When Database Systems Meet The Grid - Gray, Jim (2004)
We illustrate the benefits of combining database systems and grid technologies for data-intensive applications. Using a cluster of SQL servers, we reimplemented an existing grid application that finds galaxy clusters in a large astronomical database. The database implementation runs an order of magnitude faster than the earlier Tcl-C-file-based implementation on a Terabyte Analysis Machine (TAM). We discuss why and how the Grid can take advantage of databases systems.
also as MSR-TR-2004-81